Enhanced Channel Estimation Algorithm for Dedicated Short-Range Communication Systems - Xiang Li; Fuqiang Liu; Nguyen Ngoc Van (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
The Dedicated Short-Range Communication (DSRC) has been widely accepted as a promising wireless technology for enhancing traffic safety. In such DSRC-based vehicle-to-vehicle (V2V) communication systems, because of the extremely time-varying characteristic of wireless propagation channels, accurate channel estimation is essential for reliable information exchange between vehicles. In this paper, the characteristics of the propagation channel and several traditional channel estimation schemes for V2V communications are reviewed. Then, a delay-based channel-frequency-response decomposition scheme is proposed to estimate and predict the double-selective V2V channel while adhering to the IEEE 802.11p standard. The proposed method achieves a more favorable performance than the traditional methods in V2V scenarios by combining the least square estimation in the frequency domain with the linear prediction in time domain. The performance advantages of the proposed scheme are verified by the simulation results from three typical scenarios. Furthermore, a reference design on a field-programmable gate array for the proposed channel estimation scheme is presented for the purpose of demonstrating its implementation feasibility and complexity.